Działalność Juliusza Poniatowskiego na polu agronomii społecznej w latach 1934–1939 - Matusiak, Marcin (Zeszyty Wiejskie, 2013)
The following article is an attempt to present one of the not well-known Juliusz Poniatowski’s fields of activity during his tenure as the Minister of Agriculture and Agrarian Reforms (1934–1939). The ministerial activity of the hero in the social agronomy was conducted in parallel with the reconstruction of the agricultural system of the Polish countryside. J. Poniatowski’s key initiatives in this area included the creation of the institutions such as the National Institute for Rural Culture and the Committee of Small Farms Organisation, to which he invited to cooperation the eminent academics and peasants’ officials